The circular economy - Fullerton, Don (CESifo, 2024)
Research about the circular economy is dominated by engineers, architects, and social scientists in fields other than economics. The concepts they study can be useful in economic models of policies – to reduce virgin materials extraction, to encourage green design, and to make better use of products in ways that reduce waste. This essay attempts to discuss circular economy in economists’ language about market failures, distributional equity, and policies that can raise economic welfare by making the appropriate tradeoffs between fixing those market failures and achieving other social goals.
10419/300037
Keywords: Graue Literatur; disposal; dumping; environment; extraction; litter; policy; product design; recycling; remanufacturing; repair; reuse; social justice; sustainability